IMPLEMENTATION OF THE STUNTING RATE REDUCTION PROGRAM IN PANDEGLANG REGENCY - Aulia Dewi Purbasari; Ayuning Budiati; Arenawati Arenawati (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2026)
Stunting is a chronic nutritional problem that seriously impacts children's physical growth and cognitive development, and contributes to an increased risk of morbidity and mortality. Although the national prevalence of stunting shows a downward trend, the stunting rate in Pandeglang Regency remains relatively high, reaching 27.4% in 2022, exceeding the national and provincial averages. The Pandeglang Regency Government has implemented various stunting reduction programs through a convergence approach of specific and sensitive interventions. However, program implementation still faces various obstacles, such as limited resources, weak intersectoral coordination, low community participation, and a complex bureaucratic structure. This study aims to examine the implementation of the stunting reduction program by the Pandeglang Regency Health Office using George Edward III's policy implementation theory approach, which includes variables such as communication, resources, implementer disposition, and bureaucratic structure. This study uses qualitative methods to gain an in-depth and objective understanding of program activities through interviews, observation, and documentation. Data collected include written and spoken words, as well as observed actions, and is expected to represent actual conditions in the field. The research results show that the implementation of the stunting reduction program in Pandeglang Regency is highly integrated and has gradually succeeded in reducing stunting rates. Factors influencing the success of this implementation include communication, which in this case needs to be slightly improved and continuously enhanced. Resources, including human resources, are already very adequate in terms of both quality and quantity. Meanwhile, budgetary resources are sufficient and can support optimal program implementation. Policy implementers are dispositioned to have an appropriate team, strong commitment, and clear standard operating procedures (SOPs). The bureaucratic structure implements hierarchical coordination and conducts regular monitoring and evaluation.